Educação escolar indígena, intercultura e formação de professores (as). - Maders, Sandra (2017)
This research work, which I present as a requirement for obtaining a PhD in Education, in the Training and Knowledge and Professional Development Line (PPGE-UFSM), is a continuation of the Master's Degree in Education research developed at this same institution. This work seeks to offer theoretical and epistemological subsidies for Teacher Education in general and for Indigenous School Education in particular, based on the propositions of Biology of Knowing and Biology of Amar, that is, from the biological- Relationship in an intercultural dialogue perspective. For the development of this PhD work, qualitative research activities were carried out: documentary, of a theoretical-epistemological nature. This perspective is in agreement with the methodological proposition that research in the social sciences is of an eminently qualitative character (MINAYO 1989; DEMO 1990; COSTA, 2002). The reference framework that guided the researcher's "investigative and reflective look" (BARCELOS, 2005) in the sense of "research information production" (JACQUES GAUTHIER, 1998) is to establish dialogues that favor intercultural aspects (CANCLINI, 2003a ) With imagery and representations on the issues of indigenous culture and the training of teachers in general and in particular for indigenous school education. I believe that this work can contribute to thinking about a differentiated teacher training, since it will be in search of alternatives to deal with the challenges posed to education, taking into account the intense transformations that occurred in the world today. Thus, one of the main objectives of this research was to demystify the image we have built throughout our history on the Indians, as well as to deepen the contributions of some epistemological propositions of the thinker Humberto Maturana for the construction of a more solidary education with the indigenous communities. An education that promotes the respectful construction of cultural dialogue. The studies show that, in order for Indigenous School Education to take place in these principles of solidarity, attention must be paid to emotions such as caring for, listening to and accepting differences, both in school and in society in general, always seeking to Perspective of intercultural dialogue.